Penjagaan pesakit Buddha di Malaysia: perspektif Islam tentang penjagaan kesihatan cekap budaya = Care for buddhist patients in Malaysia : Islamic perspectives efficient cultural healthcare - Mohamad Ismail, Mohamad Firdaus; Mokhtar, Ahmad Effat; Shahadan, Siti Zuhaidah (Journal of Islamic, Social, Economics and Development (JISED), 2024)
Nurses address various needs for good health. Transcultural nursing is crucial in healthcare, ensuring culturally congruent care regardless of the patient's background. Cultural competence is vital, taking into consideration the cultural impact on health perceptions and management. Healthcare providers in Malaysia, predominantly Malay Muslim nurses, must understand the cultural differences of their patients, especially Chinese Buddhists, who constitute the second-largest clientele in the healthcare sector. This study aims to develop culturally competent care guidelines rooted in Islamic principles, addressing gaps in culturally sensitive healthcare for diverse patients. The research employs a library study method focused on the Quran and Hadith (sayings of Prophet Muhammad) to explore themes related to the care of non-Muslim patients. The study identifies three main themes: a) ethics and pure values, b) cultural and religious sensitivity, and c) ethical dilemmas. This research signifies a crucial step towards forming an Islamic ethical foundation for compassionate care of non-Muslim patients in Malaysia, recognizing and addressing both ethical dilemmas and the richness of cultural and religious diversity in the healthcare landscape. Future research should focus on assessing the effectiveness of these guidelines in enhancing the quality of care for non-Muslim patients.